Renal and immunological effects of occupational exposure to inorganic mercury. Issue 6 (June 1992) - Langworth, S; Elinder, C G; Sundquist, K G; Vesterberg, O
Abstract : Seven parameters of renal dysfunction (urinary excretion of albumin, orosomucoid, beta 2-microglobulin, N-acetyl-beta-glucosaminidase (NAG), and copper; serum creatinine concentration, and relative clearance of beta 2-microglobulin) were examined in a group of chloralkali workers exposed to mercury vapour (n = 89) and in an unexposed control group (n = 75). Serum concentrations of immunoglobulins (IgA, IgG, IgM) and auto-antibodies towards glomeruli and other tissues were also determined. The parameters examined were compared between the two groups and related to different exposure parameters. In the chloralkali group median blood mercury concentration (B-Hg) was 55 nmol/l, serum mercury (S-Hg) 45 nmol/l, and urine mercury concentration (U-Hg) 14.3 nmol/mmol creatinine (25.4 micrograms/g creatinine). Corresponding concentrations for the control group were 15 nmol/l, 4 nmol/l, and 1.1 nmol/mmol creatinine (1.9 micrograms/g creatinine) respectively. None of the parameters of renal dysfunction differed significantly between the two groups, but there was a tendency to increased excretion of NAG in the exposed group compared with the controls. Also, a statistically significant relation existed between U-Hg and U-NAG (p less than 0.001). Serum immunoglobulin concentrations did not differ between the groups, and serum titres of autoantibodies (including antiglomerular basement membrane and antilaminin antibodies) were low in both groups. Thus the results gave no evidence of glomerular damage or of a tubular reabsorption defect at the current relatively low exposures. The findings still indicate slight, dose related tubular cell damage in the mercury exposed group. There were no signs of a mercury induced effect on the immune system.